2014
DOI: 10.1080/00207543.2014.961210
|View full text |Cite
|
Sign up to set email alerts
|

Application of a hybrid dynamic MCDM to explore the key factors for the internal control of procurement circulation

Abstract: Decisions related to the internal control measurement of procurement circulation are inherently multiple criteria decisionmaking problems and are strategically important to enterprises. Although efforts have been made to discover systematic methods for enhancing purchasing performance, the criteria have been assumed to be independent, which is not actually the case. Most conventional decision models cannot capture the complex interrelationships the criteria. Here, we propose a workable hybrid dynamic multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…32 It is important to diminish the gaps between real performance values and aspiration levels and then rank the gaps for improvement alternatives in order to obtain a higher bene¯t. 33 The VIKOR method was developed from L p Àmetric, which was used as an aggregating function in a compromise programming method. 34 VIKOR uses the class distance function based on the concept of the aspiration level solution and the worst level solution and orders the results.…”
Section: Vikor Methods For Ranking and Improving The Alternativesmentioning
confidence: 99%
“…32 It is important to diminish the gaps between real performance values and aspiration levels and then rank the gaps for improvement alternatives in order to obtain a higher bene¯t. 33 The VIKOR method was developed from L p Àmetric, which was used as an aggregating function in a compromise programming method. 34 VIKOR uses the class distance function based on the concept of the aspiration level solution and the worst level solution and orders the results.…”
Section: Vikor Methods For Ranking and Improving The Alternativesmentioning
confidence: 99%
“…In this paper, the DEMATEL method is adopted into the ANP method to generate the un-weighted super-matrix. Therefore, this research combined the advantages of ANP and DEMATEL to solve the problems of dependence and feedback associated with the interrelations between criteria (Chen 2015; Chen et al 2015; Kim and Kim 2015). …”
Section: Building a Novel Madm Model For Technology And Financial Sermentioning
confidence: 99%
“…This method is used as the basic concept of the TOPSIS method (Hwang, Yoon 1981) on Euclidean distances to the positive ideal (this research adopts the aspiration level) and the negative ideal (this research adopts the worst level) solutions, and TOPSIS used the class Euclidean distance function (Yu 1973), as based the concept of the positive ideal and negative ideal solutions; then Opricovic and Tzeng (2004) found that the TOPSIS method cannot be used in ranking or selection, and proposed the VIKOR method to replace the TOPSIS method, by comparing the preference distance of all real alternatives in order to stay close to the positive-ideal point; however, this research adopted the basic idea of the traditional thinking of the VIKOR method to replace staying close to the aspiration level (Liu et al 2012;Chen 2015;Hu et al 2015). The gap concept measures the proximity to the positive ideal point in order to modify the aspiration level point.…”
Section: Modified Vikor Methodsmentioning
confidence: 99%